(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
International Public Sector Accounting Standards (IPSAS) have become one of the popular tools implemented by governments to ensure transparency on a global scale. This research evaluates the contribution of control mechanisms to the reliability of public financial and accounting information in the era of IPSAS adoption and introduces the new guidelines to be put in place in order to achieve a higher level of transparency and hence reliable public financial information that is comparable with previous years and with information from other governments in the world.